2007
DOI: 10.1186/1471-2458-7-288
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay in asylum centres and mental health in asylum seekers: a retrospective study from Denmark

Abstract: Background: The length of stay in asylum centres is generally mentioned as a possible health risk to asylum seekers. Medical staff working with asylum seekers has claimed that long lengths of stay in asylum centres might cause or aggravate mental disorders. We used records from a large, multiethnic group of asylum seekers to study if the incidence of mental disorders increased with length of stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 10 publications
3
65
0
4
Order By: Relevance
“…When the study Refugee children from the Middle East was carried out, the existing knowledge regarding the association between asylum seeking and mental health was limited. Subsequently, repeated studies of adult asylum seekers have suggested an association between refugee status and asylum seeking and poor mental health (96)(97)(98)(99)(100)(101)(102)(103)(104)(105). In addition, later studies have confirmed that asylum-seeking children suffer from poor mental health as well; for instance, 58% of the 11-16-year-old asylum seekers in Denmark were found to have signs of a mental illness (106) according to a combination of information from teachers and the children themselves.…”
Section: Mental Health In Young Refugeesmentioning
confidence: 99%
“…When the study Refugee children from the Middle East was carried out, the existing knowledge regarding the association between asylum seeking and mental health was limited. Subsequently, repeated studies of adult asylum seekers have suggested an association between refugee status and asylum seeking and poor mental health (96)(97)(98)(99)(100)(101)(102)(103)(104)(105). In addition, later studies have confirmed that asylum-seeking children suffer from poor mental health as well; for instance, 58% of the 11-16-year-old asylum seekers in Denmark were found to have signs of a mental illness (106) according to a combination of information from teachers and the children themselves.…”
Section: Mental Health In Young Refugeesmentioning
confidence: 99%
“…Secondary gain in PTSD is not exclusive to asylum-seekers (Hall and Hall, 2007). Attempts to treat asylum-seekers with PTSD are complicated by postdisplacement factors that aggravate psychological distress, such as ongoing detention (Hallas et al, 2007). The number of additional factors to be taken into consideration when treating refugees and asylum-seekers suggests that clinical guidelines drawn from research almost exclusively carried out among North Americans and Europeans (Bisson and Andrew, 2007;Stein et al, 2006) cannot be assumed to apply to refugees.…”
mentioning
confidence: 99%
“…Regarding the performance skills, especially AMPS process skills have shown to deteriorate during detention (4). Moreover, health and well-being have been found to deteriorate even further during long detentions in asylum centres (4,10,11).…”
Section: Introductionmentioning
confidence: 99%